Physician Related Delays in the Diagnosis of Lung Cancer in India - Krishnappriya Ramachandran (Journal of Clinical and Diagnostic Research, 2016)
Introduction: Lung cancer is associated with a poor prognosis, if detected late in the disease course. Delay in seeking health care, wrong diagnosis and delay in specialist referral can contribute to delay in diagnosis. Aim: This study was done to assess physician related delays in the diagnosis of lung cancer and the treatments given before presenting to our center. Materials and Methods: A total of 96 consecutive patients diagnosed with lung cancer were enrolled in this study. Details of previous physician consultations, their specialization, diagnoses made and treatments given were obtained from records available with the patients. Results: Patients, on an average consulted two physicians before presenting to our center. Less than half of the physicians (45%) suspected lung cancer during their evaluation. Around 18% of physicians made an incorrect diagnosis of tuberculosis, out of whom, 88.6% had prescribed anti-tuberculous therapy. Only 27% of physicians referred the patients to higher medical centres for evaluation. Pulmonology Specialists (PS) were the most likely to diagnose lung cancer (p<0.0001). General Medicine Specialists (GMS) were the most likely to misdiagnose cancer as tuberculosis, followed by General Practioners (GP) when compared to PS (p-value =0.0422). Conclusion: Our study demonstrates that, many physicians have a low index of suspicion to diagnose lung malignancy and most commonly misdiagnose it as tuberculosis. It is likely that most patients failed to seek the services of PS directly or through referral either due to a shortage of PS or due to other reasons.